Analisis Pelaksanaan Permenkominfo No. 5/2020 terhadap Pasal 28f/1945 dan Maqashid Syariah - Nurul Fadillah; Rusdi Hamka Lubis (Prodi Ahwal Syakhsiyah, Fakultas Syariah, Institut PTIQ Jakarta, 2022)
This study aims to analyze the implementation of the Regulation of the Minister of Communication and Informatics Number 5 of 2020 concerning Private Electronic System Operators against Article 28F of the 1945 Constitution of the Republic of Indonesia concerning the right to obtain information and how the views of the concept of maslahat in maqashid sharia relate to the implementation of these regulations. This regulation has the main focus of requiring all electronic system operators, both local and foreign, operating in Indonesia to register with the government. If you do not register, the government will terminate access to the electronic system in question. This has been proven a few months ago, where the government has cut off access to several digital platforms that have not registered, such as paypal, yahoo, epic games, steam, DOTA games, CS games, and origin (EA), even though they will be reopened in the future. because it drew a lot of criticism from citizens for the termination of access. So that the implementation of this regulation is still considered less effective. The method used in this study is a literature review and a normative juridical approach to answering problems based on a scientific perspective. The results of this study indicate that there is conformity in the implementation of Minister of Communication and Information Regulation Number 5 of 2020 with the concept of Maqasid Syariah, even though the fulfillment of information rights for citizens has not been fully fulfilled in several aspects.